Giant photoluminescence enhancement in MoSe2 monolayers treated with oleic acid ligands. Issue 14 (21st June 2021) - Tanoh, Arelo O. A.; Alexander-Webber, Jack; Fan, Ye; Gauriot, Nicholas; Xiao, James; Pandya, Raj; Li, Zhaojun; Hofmann, Stephan; Rao, Akshay
Abstract : Following our previous work on WS2 surface treatment with oleic acid (OA), we show that OA also greatly improves the optoelectronic characteristics of MoSe2 . Optical and electronic measurements point to selenide vacancy passivation by OA ligands. Abstract : The inherently low photoluminescence (PL) yields in the as prepared transition metal dichalcogenide (TMD) monolayers are broadly accepted to be the result of atomic vacancies ( i.e., defects) and uncontrolled doping, which give rise to non-radiative exciton decay pathways. To date, a number of chemical passivation schemes have been successfully developed to improve PL in sulphur based TMDs i.e., molybdenum disulphide (MoS2 ) and tungsten disulphide (WS2 ) monolayers. Studies on solution based chemical passivation schemes for improving PL yields in selenium (Se) based TMDs are however lacking in comparison. Here, we demonstrate that treatment with oleic acid (OA) provides a simple wet chemical passivation method for monolayer MoSe2, enhancing PL yields by an average of 58-fold, while also improving spectral uniformity across the material and reducing the emission linewidth. Excitation intensity dependent PL reveals trap-free PL dynamics dominated by neutral exciton recombination. Time-resolved PL (TRPL) studies reveal significantly increased PL lifetimes, with pump intensity dependent TRPL measurements also confirming trap free PL dynamics in OA treated MoSe2 . Field effect transistors show reduced charge trap density and improved on–off ratios after treatment with OA. These results indicate defect passivation by OA, which we hypothesise as ligands passivating chalcogen defects through oleate coordination to Mo dangling bonds. Importantly, this work combined with our previous study on OA treated WS2, verifies OA treatment as a simple solution-based chemical passivation protocol for improving PL yields and electronic characteristics in both selenide and sulphide TMDs – a property that has not been reported previously for other solution-based passivation schemes.